NIMG-59. EVALUATION OF THE RESPONSE ASSESSMENT CRITERIA IN NEWLY DIAGNOSED AND RECURRENT GLIOBLASTOMA. (14th November 2022) - Youssef, Gilbert; Rahman, Rifaquat; Bay, Camden; Wang, Wei; Lim-Fat, Mary Jane; Arnaout, Omar; Bi, Wenya Linda; Cagney, Daniel; Chang, Yuh-Shin; Cloughesy, Timothy; DeSalvo, Matthew; Ellingson, Benjamin; et al.
Abstract: BACKGROUND: We sought to compare the Response Assessment in Neuro-Oncology (RANO), modified RANO (mRANO), and immunotherapy RANO (iRANO) in a large population of patients with newly diagnosed (nGBM) and recurrent (rGBM) glioblastoma. METHODS: Bidimensional measurements of enhancing disease and FLAIR sequence evaluation were performed by two independent readers on brain MRIs of consecutive patients with IDH-wildtype nGBM and rGBM treated at a single institution. Discrepancies were evaluated by a third reader. Dates of disease progression (PD) were identified using RANO, mRANO, iRANO, and other response assessment criteria variations. Spearman's correlations between PFS and OS were calculated using iterative multiple imputations for censored observations. RESULTS: 526 nGBM and 580 rGBM cases were included. Spearman's correlations were not significantly different between RANO and mRANO in nGBM (0.69 [95% CI 0.62 to 0.75] vs. 0.67 [0.60, 0.73]) and rGBM (0.48 [0.40, 0.55] vs. 0.50 [0.42, 0.57]). Evaluation of FLAIR did not improve the correlation in patients who received antiangiogenic therapy. Acquisition of confirmation scans was associated with increased correlation only when PD was identified within 12 weeks of completion of radiation in nGBM. The use of the post-radiation MRI as a baseline was associated with increased correlation compared to use of the pre-radiation MRI in nGBM (0.67 [0.60, 0.73] vs. 0.53 [0.42, 0.62]). The correlation with iRANO was similar to RANO and mRANO among 98 patients with nGBM and 175 patients with rGBM who received immunotherapy. CONCLUSIONS: RANO and mRANO demonstrated similar correlations between PFS and OS. The evaluation of FLAIR can be omitted, while confirmation scans were only beneficial in nGBM in the first 12 weeks after completion of radiation. There was a trend in favor of the post-radiation MRI as the baseline scan in nGBM. The use of iRANO criteria did not add a significant benefit in patients who received immunotherapy.